Comparação das vias de administração oral e subcutânea de prednisolona em ratos (Rattus novergicus linhagem Wistar) infectados por Strongyloides venezuelensis para modelo de imunossupressão na estrongiloidíase murina - Couto, Bruna Patricia do (2019)
A study model used for human strongyloidiasis is the Strongyloides venezuelensis nematode, which infects wild rodents and shares common antigenic epitopes with Strongyloides stercoralis. This study aimed to compare oral and subcutaneous administration of prednisolone in the induction of immunosuppression in rats (Rattus novergicus) infected with S. venezuelensis. The rats were divided into six groups (n=36): G I: untreated and uninfected; G II: untreated and infected; G III: oral treatment and uninfected; G IV: oral treatment and infected; G V: subcutaneous treatment and uninfected; G VI: subcutaneous treatment and infected. For oral treatments, 5 mg/mL of sterilized water-diluted prednisolone (available oral formulation: prednisolone sodium phosphate) was made available to the animals three times for five consecutive days (-5 to 0, 8 to 13 and 21 to 26). For subcutaneous treatments, 10 mg/mL/kg of prednisolone (available subcutaneous formulation: methylprednisolone acetate) were given daily per 30 days. The infection was established by the subcutaneous injection of 3.000 filarioid larvae per animal. The groups were evaluated by physical, hematological, parasitological and immunological parameters The animals were weighed on days -5 (G I, G II, G III and G IV), 0, 8, 13, 21 and 30 (all groups). A survival curve of the animals was made throughout the treatment. Blood samples were collected on days 0, 8, 13, 21 and 30 to perform global and differential leukocyte count and serum samples were obtained for detection of anti-Strongyloides IgG, IgG1 and IgG2a antibodies. On days 5, 7, 8, 13, 21, 26 and 30 eggs were collected from infected animals for parasite quantification. On day 30, parasitic females were recovered from the groups of infected animals The results of the physical parameters showed that the animals treatments via subcutaneous did not showed weight gain, unlike those treated via oral. Out of the total of 6 animals from each group, only five animals from the control group G I and oral G III survived, three from the subcutaneous group G V and two from the G VI group. Hematologic analysis showed decrease of leukocytes and lymphocytes, and increase of neutrophils in animals treated via subcutaneous. Animals treated orally showed on days 13, 21 and 30 decrease in leukocyte count, but lymphocytes and neutrophils remained unchanged. There were no changes in eosinophils, monocytes and basophils in the control groups or in the treated groups. By the parasitological analysis, it was observed that the higher egg elimination was observed in the animals of the group treated orally, having their peaks on days 7, 13, 26 and 30 in relation to the control. There were more females recovered from the animals of the group treated orally. Immunological analysis showed that there was not production of IgG, IgG1 and IgG2a in immunosuppressed animals by subcutaneous route. It can be concluded that treatment with prednisolone administered by route oral and subcutaneous was able to produce suppressive effects in animals infected or not with S. venezuelensis. Immunosuppression by the oral route acts directly on the parasite causing greater elimination of eggs and increase in the number of parasitic females. Immunosuppression by the subcutaneous route modulates the immune system of the host, and can be observed by global and differential leukocyte count and decreased humoral response.